Expression of CDC42 in cervical squamous cell carcinoma and its correlation with clinicopathologic characteristics - Ma, Ding; Cheng, Yuan; Zhang, Youyi; Guo, Yanli; Li, Zijian; Li, Geng (Chinese Journal of Cancer Research; Vol 25, No 6 (December 26, 2013): Chinese Journal of Cancer Research, 2013)
Objective: The high expression of cell division cycle 42 protein (CDC42) may be involved in the occurrence and progression of several tumors. However, the expression and function of CDC42 in cervical squamous cell carcinoma remains unclear. This study aimed to investigate the expression of CDC42 in cervical squamous cell carcinoma and its correlation with clinicopathologic characteristics. Methods: The expression of CDC42 in 162 cervical squamous cell carcinoma tissue samples and 33 normal cervical tissue samples was investigated by immunohistochemistry. The CDC42 mRNA expression was detected by reverse transcription-polymerase chain reaction (RT-PCR). Results: The cervical squamous cell carcinoma group showed a significantly higher CDC42 positive rate, compared to the normal cervical tissues (P0.05). Furthermore, compare with normal cervical tissues, the CDC42 mRNA expression in cervical cancer had no significant difference. Conclusions: CDC42 was up-regulated at protein level, but not mRNA level, in cervical squamous cell carcinoma. The high expression of CDC42 was correlated to the clinical stage of the patients, indicating that CDC42 might contribute to the progression of cervical squamous cell carcinoma.